2005
DOI: 10.1007/s10646-005-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Damage in Two Species of Aquatic Turtles (Emys orbicularis and Mauremys caspica) Inhabiting Contaminated Sites in Azerbaijan

Abstract: The Caspian region and specifically the Apsheron peninsula of Azerbaijan are known to be polluted with a variety of environmental contaminants. These complex mixtures of contaminants make risk assessment difficult. We used the flow cytometry method (FCM) and the micronucleus assay (MN) to assess chromosomal damage in aquatic turtles (Emys orbicularis, the European pond turtle; and Mauremys caspica, the Caspian turtle) inhabiting contaminated wetlands in Azerbaijan. Evidence of genetic damage was found for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 65 publications
2
40
1
3
Order By: Relevance
“…At sediment and tissue concentrations measured more than 3 orders of magnitude higher than the present study, summed PAHs were implicated in increased deformities in common snapping turtles (Chelydra serpentina) and painted turtles (Chrysemys picta) in Philadelphia, Pennsylvania (Bell et al, 2006). Moreover, sediment PAH concentrations 1 to 2 orders of magnitude greater than reported in the present study were associated with genotoxicity in turtles (Matson et al, 2005). To our knowledge, this is the first study to measure plasma PAH concentrations in freshwater turtles.…”
Section: Discussioncontrasting
confidence: 59%
“…At sediment and tissue concentrations measured more than 3 orders of magnitude higher than the present study, summed PAHs were implicated in increased deformities in common snapping turtles (Chelydra serpentina) and painted turtles (Chrysemys picta) in Philadelphia, Pennsylvania (Bell et al, 2006). Moreover, sediment PAH concentrations 1 to 2 orders of magnitude greater than reported in the present study were associated with genotoxicity in turtles (Matson et al, 2005). To our knowledge, this is the first study to measure plasma PAH concentrations in freshwater turtles.…”
Section: Discussioncontrasting
confidence: 59%
“…Reptiles, being poikilothermic vertebrates, can be used as nonstandard bioindicators for assaying natural populations to investigate the presence of pollutants and mutagens in the environment (Matson et al 2005;Strunjak-Perović et al 2010). Moreover, by analyzing the hematology and blood biochemistry of reptiles, we can get a picture of the hemoparasite load in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al, 2008;Matson et al, 2005;. Rinner et al (2011) identified increased rates of mutation associated with contaminant exposure in an invasive fish species in a highly contaminated region in Azerbaijan.…”
Section: Contaminant-induced Increases In Mutation Ratesmentioning
confidence: 96%